Modulation of Neutrophil Apoptosis and the Resolution of Inflammation through β2 Integrins - El Kebir, Driss; Filep, Janos G. (Frontiers in Immunology, 2013)
Precise control of the neutrophil death program provides a balance between their defence functions and safe clearance, whereas impaired regulation of neutrophil death is thought to contribute to a wide range of inflammatory pathologies. Apoptosis is essential for neutrophil functional shutdown, removal of emigrated neutrophils and timely resolution of inflammation. Neutrophils receive survival and pro-apoptosis cues from the inflammatory microenvironment and integrate these signals through surface receptors and common downstream mechanisms. Among these receptors are the leukocyte-specific membrane receptors β2 integrins that are best known for regulating adhesion and phagocytosis. Accumulating evidence indicate that outside-in signaling through the β2 integrin Mac-1 can generate contrasting cues in neutrophils, leading to promotion of their survival or apoptosis. Binding of mac-1 to its ligands ICAM-1, fibrinogen or the azurophilic granule enzyme myeloperoxidase suppresses apoptosis, whereas Mac-1-mediated phagocytosis of bacteria evokes apoptotic cell death. Mac-1 signaling is also target for the anti-inflammatory, pro-resolving mediators, including lipoxin A4, aspirin-triggered lipoxin A4 and resolvin E1. This review focuses on molecular mechanisms underlying Mac-1 regulation of neutrophil apoptosis and highlights recent advances how hierarchy of survival and pro-apoptosis signals can be harnessed to facilitate neutrophil apoptosis and the resolution of inflammation.